Math, asked by prasib85, 2 months ago

: Multiply -6ab with (5ba -18abc)​

Answers

Answered by ISAlishaTripathy
1

Answer:

Tha answer is

108 {a}^{2}  {b}^{2} c - 30 {a}^{2}  {b}^{2}

Step-by-step explanation:

 (- 6ab) \times (5ba - 18abc) \\  =  - 6ab \: (5ba - 18abc) \\  =  - 30 {a}^{2}  {b}^{2}  + 108 {a}^{2}  {b}^{2} c \\  = 108 {a}^{2}  {b}^{2} c - 30 {a}^{2}  {b}^{2}

Answered by sathiyasenthil121985
0

Answer:

the answer is :

( -6ab ) × ( 5ba - 18 abc )

= -6ab ( 5ba - 18 abc )

= -30a²b² + 108a²b²c

= 108a²b²c - 30a²b²

PLEASE MARK ME AS BRILLIANT

Similar questions